Numerical and experimental investigation of heat transfer in liquid cooling serpentine mini-channel heat sink with different new configuration models. (June 2018) - Imran, Ahmed Abdulnabi; Mahmoud, Nabeel Sameer; Jaffal, Hayder Mohammad
Highlights: Cooling of electronic chips. Serpentine mini-channel heat sink. Computational fluid dynamics technique. Thermal resistance. Different New Configuration Models. Abstract: Cooling of electronic chips has become a basic viewpoint in the advancement of electronic devices. Overheating may cause glitch or harm to hardware. A water-cooled mini-channel is a successful cooling innovation for cooling of heat sinks. In this work, geometric optimisation of a 3D serpentine mini-channel heat sink (SMCHS) was investigated. Four configurations of SMCHS were proposed. These configurations were then simulated numerically and tested experimentally. Finite volume method computational fluid dynamics technique is used to model single-phase forced convection for water-cooling laminar flow in a 3D mini-channel heat sink with various channel configurations. Experiments were conducted to analyse the effect of water mass flow rate and heat load on thermal and hydraulic performances of the SMCHS. Experimental results agree well with numerical results. Results indicate that the performance of the proposed device effectively improves when serpentines with two inlets and two outlets are used compared with conventional serpentine with one inlet and one outlet.